Internal Communication and Brand Community: Lessons from a Digital Start-Up Company - Ananda Fortunisa; Riska Dwinda Elsyah (Jobmark: Journal of Branding and Marketing Communication, 2020)
This article examines the relationship between internal corporate communication and brand community for millennial employees at digital startup companies in Jakarta. The research method uses a mixed approach with qualitative and quantitative tests. The qualitative test uses the interview method to find out the description of the internal corporate communication formed by the company to millennial employees and its relation to the process of brand community activities involving millennial employees. A quantitative test is used to test the model between internal corporate communication and brand community. The dimensions of the internal corporate communication variable refer to brand message effectiveness, brand feedback, and communication channels, while the measurements of the brand community variable refer to the experience of information, socialization, human-machine interaction, and entertainment. The results of this study indicate that there is a strong influence between the company's internal communication management on brand community activities.